Analisis Sistem Virtual Cluster Pada Komputasi Paralel Menggunakan Layanan IAAS - Retnani, Diah Ayu; Alwi, Erick Irawadi (Program Studi Sistem Informasi - Universitas Jember, 2016)
Industrial technology development needed solutions about increasing computing resource performance. The one of alternative solution could resolve this problem using the high performance computingâs concept example cluster. Cluster could increase performance of computing using many integrated computers in the computer network. cluster had problem in infrastructure system example place and hardware. One of the alternative solutions was virtual computer for infrastructure. one of cloud system services was IAAS. IAAS could produce integrated virtual computation resource on network directly. This study discussed about virtual clusterâs performance using the virtual computer to solve the parallel computingâs problem. Virtual computer in this study used cloud services. The research method was by implementing OpenMPI on a Linux-based computer cluster using five virtual computer and analyzed the performance of the system by different scenario tests. The results of this study Showed that the cloud was able to facilitate user to provide integrated infrastruktures computing service on a network-based and the virtual cluster machine was suitable when large size of data. Ideally, the value of speedup increased when the number of processors increases. The value of Speed-up was ideal when the the data size of 1000 using two nodes (1,346) and three nodes (1.0465). The value of Efficiency decreases when increasing number of processors. Most of the Value of speed-up and efficiency were not ideal at this experiment Because there was the overhead in the parallel system, for example, the additional parallel computing, inter-processor communication and synchronization processes in the cloud as provider of virtual computers.